Definition diagnosis and treatment of neuropathic pain - Schestatsky, Pedro (2009)
Neuropathic Pain is defined as pain caused by lesion or dysfunction of the nervous system, as a result of abnormal activation of the nociceptive pathway (small fibers and spinothalamic tracts). The most common causes of this syndrome are the following: diabetes, post-herpetic neuralgia, trigeminal neuralgia, complex regional pain syndrome, stroke, multiple sclerosis, spinal cord injury, among others. In the last few years, the Neuropathic Pain, has been receiving special attention for two main reasons: 1) therapeutical refractoriness of a variety of pain syndromes with predominant neuropathic characteristics and 2) the development of diagnostic tools for Neuropathic Pain complaints. The present paper provides relevant information on the understanding and recognition of Neuropathic Pain, as well as therapeutic evidence-based-medicine approaches.